2017
DOI: 10.1016/j.ihj.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of nitroglycerin and verapamil solution by organ bath technique in preparation of left internal thoracic artery for coronary artery bypass surgery

Abstract: BackgroundThe aim of this prospective study was to compare the effect of application of nitroglycerin and verapamil solution (GV) by organ bath technique with other methods of applications and solutions on the free blood flow of LITA. The technique was not described for in situ graft before.MethodThe patients were randomly assigned to four groups: group I (n_32, GV solution by organ bath technique), group II (n_30, papaverine solution by organ bath technique), group III (n_29, topical GV solution) or group IV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
0
0
2
Order By: Relevance
“…Several studies have demonstrated that verapamil-containing solutions do not cause lasting impairments in vasodilatory function. 10 22 23…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that verapamil-containing solutions do not cause lasting impairments in vasodilatory function. 10 22 23…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that verapamilcontaining solutions do not cause lasting impairments in vasodilatory function. 10,22,23 It would be ideal to study the effects of papaverine, lidocaine, and verapamil using arterial samples from additional groups of participants (e.g., healthy, young, and old), but it is difficult to obtain samples from such groups. Therefore, the patients in the current study had a history of breast cancer and therapy (chemotherapy, endocrine therapy, or radiation therapy), which is representative of the majority of patients undergoing the DIEP flap procedure.…”
Section: Lasting Effects Of Papaverine Lidocaine and Verapamil On End...mentioning
confidence: 99%
See 1 more Smart Citation
“…Greftin erken ve geç dönem açıklığını artırmak amacıyla sistemik nitrogliserin-diltiazem, topikal papaverin, topikal milrinon, verapamil-nitrogliserin kombinasyonu gibi farmakolojik yöntemler ve organ banyosu gibi farklı cerrahi tekniklerin yanı sıra anestezistler tarafından gerçekleştirilen stellat ganglion bloğu gibi yaklaşımlar tanımlanmıştır [9] . Chandran R. ve ark.…”
Section: öRneklem Büyüklüğü Ve İstatistiksel Analizunclassified
“…Fakat geniş serili çalışmalar ile bu risklerin ortaya çıkma olasılığı ortaya konabilir. Her ne kadar günümüzde papaverin uygulamasında etkin ve güvenli oluşu nedeniyle topikal uygulama genel kabul gören yöntem olsa da organ banyosu gibi farklı modifikasyonlar ile en etkin yöntem arayışı devam etmektedir [9] .…”
Section: öRneklem Büyüklüğü Ve İstatistiksel Analizunclassified